Transition In, Transition Out (TiTo) : Peer Mentoring for Sustainable Development of First and Third Year Psychology Students : Final Report. - Chester, Andrea; Burton, Lorelle; Xenos, Sophia; Elgar, Karen; Denny, Bianca (Office for Learning and Teaching, 2013)
This project proposes a unique, sustainable solution to issues arising for students in the transition into and out of undergraduate programs. Bringing transitioning students together in peer mentoring relationships embedded in the curriculum simultaneously supports first year students and develops third year students. The theoretical framework for the project is Lizzio's (2006) 'five senses of student success' model. The five senses, which predict student success in first year, provide the framework for the first year mentoring program designed to support students on their first assessment tasks. In a novel application, the five senses will also guide the training and development of third year mentors, supporting development of graduate attributes and professional identity. The project compared outcomes for students enrolled in face-to-face delivery of psychology courses at a large metropolitan university with those at a smaller regional university learning via a blended model. Although the project is psychology-focused, its outcomes have application across higher education.